Numerical Modeling Analysis of Tsunami Inundation in the Coastal Area of Ngadirojo, Pacitan Regency - Muhamad Rakif Panguale; Muhammad Fiky Izzulhaq; Chezta Ahmad Muzakky (Politeknik Negeri Batam, 2026)
Coastal communities along the southern coast of Java are increasingly vulnerable to tsunami hazards due to active seismotectonic conditions in the Indian Ocean. This study presents a comprehensive numerical modeling analysis of the tsunami inundation map in the Ngadirojo coastal area of Ngadirojo Subdistrict, Pacitan Regency, East Java. The research objectives are to simulate potential tsunami scenarios, map inundation extents, and assess coastal vulnerability for disaster risk reduction planning. The Cornell Multi-grid Coupled Tsunami Model (COMCOT) is employed to simulate tsunami propagation and coastal inundation using high-resolution bathymetric and topographic data. The modeling incorporates nested grid systems with spatial resolutions ranging from 1250 m in deep ocean to 10 m in nearshore areas. The study provides a detailed analysis using numerical modeling techniques for predicting tsunami wave heights, inundation distances, and arrival times with a single earthquake source scenario of maximum magnitude Mw 8.8 in the Pacitan coastal region. Results indicate that tsunami waves could reach a maximum height of 16.4 m, with inundation extending up to 3.98 km inland and arrival times as short as 30 minutes. The derived tsunami hazard index highlights extensive high-risk zones along Soge and Taman Ngadirojo Beaches. The study provides essential scientific data to help local authorities develop effective evacuation strategies, early warning systems, and coastal protection measures, and significantly contributes to tsunami risk assessment methodologies for similar coastal environments in Indonesia and the Indo-Pacific region.